Learning by doing and learning from others in contraceptive technology - Jungho Kim (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2005)
This paper provides a theoretical and empirical investigation of the impact of social learning on modern contraceptive prevalence. A theory is developed where own or neighbors' experience increases the benefit from using modern contraceptives by reducing the uncertainty regarding contraceptive efficacy. Empirical results from the Indonesian Family Life Survey suggest that the more own experience of modern contraceptives a woman has she is more likely to use those methods. However, neighbors' experience does not have a significant impact on one's current usage of contraceptives. One explanation of these findings is that the information on contraceptive efficacy, or failure rates is likely to contain much noise when women communicate with each other. These findings contrast those of recent literature, which show the adoption of contraceptives by one's social contacts has positive impact on one's own adoption.
Keywords: D83; J13; 330; Knowledge Diffusion; Social Learning; Contraceptive Technology; Indonesia; Verhütungsmittel; Wissenstransfer; Theorie; Schätzung; Indonesien; Soziale Beziehungen